Carpal Translocation Following Dorsal Bridge Plate Fixation of Distal Radius Fractures: A Cadaveric Study - Azad, Ali; Intravia, Jessica M.; Hill, J. Ryan; Leland, Hyuma; Vakhshori, Venus; Stevanovic, Milan; Ghiassi, Alidad (Journal of Wrist Surgery, 2019)
Background Dorsal bridge plate fixation is an effective technique for stabilization of highly comminuted, complex distal radius fractures. However, it is unknown whether fixation to the second or third metacarpal is optimal. Given dorsal bridge plating spans the radiocarpal joint, it is unclear if the dorsal spanning plate affects carpal position. This study investigates differences in carpal translocation resulting from bridge plate distal fixation to either the second or third metacarpal.Methods Ten paired cadaveric upper extremities without evidence of gross deformity or prior surgery distal to the elbow were evaluated with three-view wrist fluoroscopic images for baseline radiographic measurements. An unstable distal radius fracture model was created via a volar approach using a 1-cm osteotomy. Following fracture creation, a dorsal bridge plate was applied with random to the second metacarpal on one limb, and the third metacarpal on the contralateral limb. Laterality for distal fixation was chosen randomly. Fluoroscopic images were repeated and radial inclination, radial height, radiocarpal angle, volar tilt, ulnar variance, radiolunate angle, radioscaphoid angle, radial rotation index, and carpal translocation were measured.Results Radial inclination, radial height, radiocarpal angle, volar tilt, ulnar variance, radiolunate angle, and radioscaphoid angle were not statistically different before and after fixation, or when comparing the second or third metacarpal fixation. Additionally, there was no difference in Taleisnik's ulnar translocation index, Chamay's ulnar translation index, or McMurtry's carpal translation index based on which metacarpal was used for distal fixation.Conclusions Dorsal bridge plate fixation of distal radius fractures restores preoperative physiologic measures of the radius, ulna, and carpus. Carpal translocation was similar when comparing distal fixation to the second or third metacarpal in distal radius fractures stabilized with a bridge plate.Level of Evidence This is a Level V, therapeutic study.
Keywords: distal radius fracture; bridge plate; radiocarpal distraction plate; carpal translocation; cadaveric study